2015
DOI: 10.1371/journal.pone.0122638
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Traditional Medicine Use in Northern Tanzania: A Mixed-Methods Study

Abstract: IntroductionTraditional medicines are an important part of healthcare in sub-Saharan Africa, and building successful disease treatment programs that are sensitive to traditional medicine practices will require an understanding of their current use and roles, including from a biomedical perspective. Therefore, we conducted a mixed-method study in Northern Tanzania in order to characterize the extent of and reasons for the use of traditional medicines among the general population so that we can better inform pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
74
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 34 publications
8
74
1
1
Order By: Relevance
“…49 In addition, two population-based studies 48 189 and a subhealth study 192 reported that respondents were reluctant to use traditional medical care due to the perceived demonic nature of TCAM. Further, four population-based studies from Ghana 183 184 189 and Tanzania 73 and subpopulation studies from Nigeria 31 and Ghana 192 cited perceived lack of an appropriate dose for TCAM products and unhygienic practice in product preparation, 31 73 183 184 189 as well as the unregulated TCAM practitioner practice, 183 192 as deterrent to using TCAM. Other barriers to TCAM use were an absence of health financing for traditional health care 183 and a perceived lack of education and training among TCAM practitioners.…”
Section: Tcam Users Seeking Infertility Carementioning
confidence: 99%
“…49 In addition, two population-based studies 48 189 and a subhealth study 192 reported that respondents were reluctant to use traditional medical care due to the perceived demonic nature of TCAM. Further, four population-based studies from Ghana 183 184 189 and Tanzania 73 and subpopulation studies from Nigeria 31 and Ghana 192 cited perceived lack of an appropriate dose for TCAM products and unhygienic practice in product preparation, 31 73 183 184 189 as well as the unregulated TCAM practitioner practice, 183 192 as deterrent to using TCAM. Other barriers to TCAM use were an absence of health financing for traditional health care 183 and a perceived lack of education and training among TCAM practitioners.…”
Section: Tcam Users Seeking Infertility Carementioning
confidence: 99%
“…A striking feature of this patient's presentation to hospital was the first-time diagnosis of Down Syndrome. Tanzania is a low-income country with citizens having limited access to healthcare, and in a society where traditional medicine is still largely practised it is not uncommon for a spectrum of conditions to go undiagnosed for prolonged periods of time [13].…”
Section: Discussionmentioning
confidence: 99%
“…Para konsumen obat tradisional di Tanzania sebelah utara juga mengungkapkan biaya pengobatan, waktu tunggu yang lama, dan kurangnya pengalaman tenaga kesehatan di daerah mereka menjadi penyebab mereka tetap memilih pengobatan tradisional. Selain itu para konsumen juga masih memiliki pemahaman yang minim mengenai penyakit mereka (Stanifer et al 2015). Gitawati dan Handayani (2008) mengemukakan pula bahwa ada sejumlah konsumen yang merasakan efek samping dari obat tradisional seperti rasa mual, muntah, perut kembung, pusing, dan diare setelah mengkonsumsi obat tradisional.…”
Section: Karakteristik Konsumen Obat Berbahan Baku Herpetofaunaunclassified